Priority based computation: "An Initial study result of paradigm shift on real time computation" - Sukemi Sukemi; Riyanto Riyanto (Computer Engineering and Applications Journal, 2017)
This research is purposed to increase computer function into a time driven to support real time system. This purposed would the processor can work according to determined time variable and can work optimally in a certained deadline. The first approachment to design some of processor that has a different bit space 64, 32, 16 and 8 bits. Each processor will be separated by selector/arbiter priority of a task. In addition, the design of the above processors are designed as a counter with varying levels of accuracy (variable precision computing). The selection is also done by using statistical control in the task are observed by the appearance of controller mounted on the front of the architecture bit space the second approach above. The last approach to ‘add’ certainty in the form of interval arithmetic precision cutting task that can be the upper bound and lower bound of the area (bounds). These four approachment can be structured orthogonally into a processor/several processors by introducing a new classifier that serves as a selector or a task arbiter. The results of the four approaches to prove that the processor is prepared by incorporating a variable bitspace adder selectors can provide optimality of 0.43%.